Islamic law and criminology - Khan, Muhammad Moinuddin (Discovery Pub. House, 2011)
Islam, as a faith is a complete code of life, It tells its dollowers how to lead a happy and prosperous life, here and hereafter. Almighty Allah's last dan final Prophet, Muhammad (Pbuh) preached a good-for-all-times religion in this world over 1400 years back in the Arabian desert. When the Prophet (Pbuh) opened his eyes in the world, the Land of Arabian was completed engulfed in inhuman and utterly barbarous practices. There was no room for mercy and compassion in stony-hearted people of Arabian. Seeing this utterly ignoble and pathetic conduction, Allah, the Mighty and Powerpul, decided to change the age-long tradition, prevailing among the pagans. These people were not known to education, right of human beings, neighbours, parents and even the diving creator.